2019
DOI: 10.1111/jcpt.13052
|View full text |Cite
|
Sign up to set email alerts
|

Association between Opioid Dose, Acute Post‐operative Pain and Walking Distance Following Lumbar Spine Surgery

Abstract: What is known and objective: The opioid doses on post-operative day 1 (POD1) is a major predictor of recovery in patients following lumbar spine surgery (LSS). However, the opioid doses vary widely in clinical practice. Thus, the objective of this study was to explore the associations between opioid doses on POD1, pain and function during a hospital stay in patients following LSS. Methods: This study used medical records of patients who underwent LSS between January 2007 and March 2018. The patients were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated the effect of ambulation in the first week after spine surgery on long-term patient disability, physical function, and postoperative complications; however, the relationship between inpatient physical activity after ASD surgery and postoperative complications in elderly patients has not been fully explored. [3][4][5][6][7][8][9][10][11][12][13][14] The ability of the elderly patient to independently walk as early as possible following ASD surgery may decrease the perioperative complication rate. The present study examines the correlation in clinical outcomes of elderly patients with their ability to ambulate.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the effect of ambulation in the first week after spine surgery on long-term patient disability, physical function, and postoperative complications; however, the relationship between inpatient physical activity after ASD surgery and postoperative complications in elderly patients has not been fully explored. [3][4][5][6][7][8][9][10][11][12][13][14] The ability of the elderly patient to independently walk as early as possible following ASD surgery may decrease the perioperative complication rate. The present study examines the correlation in clinical outcomes of elderly patients with their ability to ambulate.…”
Section: Introductionmentioning
confidence: 99%